Respuesta :

It is a quadratic equation.

Expand the equation to find the general form

y = (x + 3)^2 - 4

y = (x + 3)(x + 3) - 4

y = x^2 + 6x + 9 - 4

y = x^2 + 6x + 5

Answer:

y = x^2 + 6x + 5

Step-by-step explanation:

Here we want to rewrite y = (x + 3)^2 - 4 in standard form, which is:

                                         y = ax^2 + bx + c

First, expand y = (x + 3)^2 - 4:

                     y = x^2 + 6x + 9 - 4

Combining like terms, we get:

                      y = x^2 + 6x + 5          which is in standard form.

This simplifies to:

                      y =

ACCESS MORE